Osmotic disruption of chromatin induces Topoisomerase 2 activity at sites of transcriptional stress - William H. Gittens; Rachal M. Allison; Ellie M. Wright; George G. B. Brown; Matthew J. Neale (Nature Communications)
Abstract Transcription generates superhelical stress in DNA that poses problems for genome stability, but determining when and where such stress arises within chromosomes is challenging. Here, using G1-arrested S. cerevisiae cells, and employing rapid fixation and ultra-sensitive enrichment, we utilise the physiological activity of endogenous topoisomerase 2 (Top2) as a probe of transcription-induced superhelicity. We demonstrate that Top2 activity is surprisingly uncorrelated with transcriptional activity, suggesting that superhelical stress is obscured from Top2 within chromatin in vivo. We test this idea using osmotic perturbation—a treatment that transiently destabilises chromatin in vivo—revealing that Top2 activity redistributes within sub-minute timescales into broad zones patterned by long genes, convergent gene arrays, and transposon elements—and also by acute transcriptional induction. We propose that latent superhelical stress is normally absorbed by the intrinsic topological buffering capacity of chromatin, helping to avoid spurious topoisomerase activity arising within the essential coding regions of the genome.